Kerangka Kerja Komprehensif: Kepatuhan Seleksi Vendor sebagai Variabel Intervensi dalam Pengaruh Bias Kognitif, Kepercayaan Digital, dan Manajemen Risiko pada Sistem Pengadaan Logistik yang Adil di PT Pos Indonesia - Bebi Ahmed Jo Pical; Melia Eka Listiani; Erna Mulyati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research develops and tests a comprehensive framework examining how cognitive bias, digital trust, and risk management influence logistics equitable procurement through vendor selection compliance as a mediating mechanism. Employing partial least squares structural equation modeling (PLS-SEM) with bootstrapping analysis on data from PT Pos Indonesia's procurement operations, the research tested ten hypotheses across 255 respondents. The findings reveal that procurement equity emerges through integrated psychological, technological, and governance pathways, with vendor selection compliance serving as a critical mediating mechanism. The research contributes novel insights into operationalizing equitable procurement systems in emerging economy logistics organizations. Practically, the research provides guidance for implementing fair, transparent, and resilient vendor selection procedures by integrating behavioral debiasing initiatives, digital infrastructure investments, and compliance enforcement mechanisms. These findings address critical gaps in understanding how multidimensional organizational interventions collectively shape procurement fairness outcomes.